Reading Societies and their Social Exclusivity: Dalmatia in the First Half of the 19th century (Libellarium: journal for research in the field of information and related sciences, 2009)
Reading societies, known as the gabinetto di lettura, or the casino, appeared in Dalmatia in the middle of the 18th century modelled on their Western European, North Italian and Austrian counterparts. They became centres of social and cultural life in the region. However, their number was very small in comparison with other Central and Western European countries. In spite of that, their statutes can serve a historian as very fertile and useful historical sources. First of all, they can reveal the importance given to books and reading as well as changing attitude towards reading in the course of time. They can also indicate social structure of the reading circles as well as the interaction and communication among the members. In addition, they can reveal the participation of women in social and cultural life, internal functioning of the society, etc. Based on the statutes of several reading societies of the 19th century, this work suggests several important issues. First, it shows that in the first half of the 19th century the membership of these societies was still select and prestigious, acquired by position on the social scale. In other words, reading societies were still confined to very narrow social circles of the educated. Although in Western parts of Europe the reading public became more heterogeneous and open, in Dalmatia reading still preserved its exclusive features. Second, the work also suggests that what some historians of book and reading called the ”reading revolution” or ”revolution in reading” occurred in Dalmatia much later, and even then mostly in urban areas. Some changes in reading habits occurred in the region, albeit to a limited extent and with less influence on society as a whole. Third, the work also demonstrates that from the 1840s reading acquired a new dimension, becoming open to the more social strata and gradually losing its exclusive character. The reading societies, lending libraries and other cultural institutions established in the course of the 1840s did not limit their memberships by the social parameters. The only criterion seems to have been activity work for the benefit of the nation and its education. Yet, it may be concluded that what had happened in most of Central and Western Europe in the late 18th century, occurred in Dalmatia only at the very end of the 19th and beginning of the 20th century. However, without an actual account of the membership of these societies and their reading habits (still missing in Croatian historiography due to a lack of information on the members and their numbers), it is difficult to give a completely accurate picture of the degree to which reading became significant in the early 19th century. Along with information on the amount of money set aside for new reading material and the increase of the library inventories (which has not yet been found), this would certainly shed new light on the importance of books and reading had in the first half of the 19th century.
Keywords: Dalmatia; 19th century; reading; reading societies; ”reading revolution”; casino; gabinetto di lettura